Delirium Motor Subtypes and Severity of Physical Symptoms in Patients with Advanced Cancer in Inpatient Hospice/Palliative Care Units: A Multicenter Prospective Cohort Study - Hasegawa, Takaaki; Mori, Masanori; Yamaguchi, Takashi; Imai, Kengo; Matsuda, Yoshinobu; Maeda, Isseki; Hatano, Yutaka; Yokomichi, Naosuke; Hamano, Jun; Morita, Tatsuya (Journal of palliative medicine, 2025)
Altered cognitive function due to delirium changes the threshold or tolerance of symptoms. The impacts of delirium motor subtypes on symptoms remain unknown. Determining whether delirium motor subtypes are associated with the severity of physical symptoms in a palliative care setting. A secondary analysis of a multicenter prospective observational study. We included consecutive patients with advanced cancer admitted to 23 inpatient hospices in Japan in 2017. Occurrence of delirium, motor subtype, and severity of pain and dyspnea (Integrated Palliative Care Outcome Scale) were assessed at admission (T1) and on the day of Palliative Performance Scale declined to 20 (T2). T1 and T2 data were obtained from 1896 and 1396 patients, respectively. Using patients without delirium as a reference, the odds ratio (OR) for moderate-to-overwhelming pain among those with hyperactive or mixed delirium was significantly higher at T1 and T2 (OR, 95% confidence interval [CI]: 1.49, 1.15-1.92, and 1.71, 1.26-2.32, respectively). A similar trend was observed for dyspnea at T1 and T2 (OR, 95% CI: 1.54, 1.16-2.06, and 1.88, 1.39-2.55, respectively). However, patients with hypoactive delirium did not have higher odds of developing severe symptoms. Patients without delirium at T1, who developed hyperactive or mixed delirium, had a higher severity of both pain and dyspnea than those who were delirium-free (OR, 95% CI; 1.60, 1.08-2.37, and 1.86, 1.27-2.72, respectively) at T2. Hyperactive delirium is associated with the intensity of pain and dyspnea in patients receiving palliative care.